GANGGUAN ARTIKULASI PADA INDIVIDU YANG MENGALAMI DISARTRIA (DILIHAT DARI PERSPEKTIF NEUROLINGUISTIK) - Rizka Damayanti; Juaidah Agustina; Masnunah (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
The problem in this study is how articulation disorders in individuals suffering from dysarthria (viewed from a neurolinguistic perspective) The study aims to find out how the condition of people suffering of dysartria suffers from articulation disturbances (viewed from a neuro-linguistic perspectives) in the village of Banu Mas, Ogan district of East Komering Ulu. This research method is using qualitative methods. The subjects in this study consisted of three people (MA), (NU), and (JU). Data analysis techniques are using observation or observation techniques, interviews, recordings, and documentation. The researchers found that there were four vocal and consonant errors that occurred in (MA), (NU), and (JU) the addition of sound (addition), distortion, omission, and substitution of sound. (substitusi). In addition to vocal sounds, two phonems were found, while the consonants found seven phonemes. In the distortion of vocal sound, the researchers found 23 phones. In vocal omission, one phonem was found, whereas in the bunny consonant, 42 phones were found